A Psychological and Social Analysis of Terrorism Vulnerability: Understanding the Predisposition and Attitudes towards Terrorism (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Terror and terrorism are tricky and often misused ideas in terms of their complicated andsometimes confusing relationship to other types of political violence and crime. Terror is a very subjectiveemotion. We all have various fear thresholds and are more readily horrified by specific experiences,images, and dangers presented by others. The interaction of these subjective elements and individualillogical, and sometimes unconscious, reactions makes terror, severe fear, or dread a particularly difficultterm for factual social scientists to grasp.The current research is concerned with various social and psychological aspects that predispose peopleto become terrorists. The proclivity for terrorism denotes a neuro-psychological preparedness forterrorist activities, a proclivity for terrorism, and a favourable attitude toward murder, looting, andmurdering innocent people in order to achieve a certain purpose.This research comprehends the social and psychological aspects that may lead to a favourable attitudetoward terrorism. Various literature and related study are being reviewed to get the final conclusion.After analysis of all content, study explored that